8H-, 10H-, 14H-SiC formation in 6H-3C silicon carbide phase transitions - Vlaskina, S.I.; Mishinova, G.N.; Vlaskin, V.I.; Rodionov, V.E.; Svechnikov, G.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
In this paper the results of photoluminescence researches devoted to phase transitions in 6H-3C-SiC have been presented. High pure 6H-SiC crystals grown by Tairov’s method with and without polytype joint before and after plastic deformation at high temperature annealing were investigated using optical spectroscopy. Low temperature photoluminescence changes in the transition phase of SiC crystal represented with the stalking fault spectra within the temperature range 4.2 to 35 K. The stalking fault spectra indicate formation of metastable nanostructures in SiC crystals (14H₁ <4334>, 10H₂ <55>, 14H₂ <77>). The phononless part of each stalking fault spectrum consists of two components of radiative recombination that are responsible for hexagonal and cubic arrangement of atoms. Each of radiative recombination components in the stalking fault spectrum has the width of entire band 34 meV and shifts relative to each other by 26 meV. The overlap area of those components equals to 8 meV. The super-fine structure of the recombination components in spectrum is observed, and it is related to different Si – Si or C – C and Si – C bonds. Behavior of all the stalking fault spectra is similar (temperature, decay of luminescence). The processes of the phase transition are explained by the mechanism of interfacial rearrangements in the SiC crystals.